A robotic device as a sensitive quantitative tool to assess upper limb impairments in stroke patients: A preliminary prospective cohort study - Gilliaux, M; Lejeune, T; Detrembleur, C; Sapin, J; Dehez, B; Stoquart, G (Journal of rehabilitation medicine, 2012)
To compare kinematic indices in age-matched healthy subjects and stroke patients, by evaluating various tasks performed with a robotic device, and to provide an objective and standardized protocol to assess upper limb impairments in stroke patients. A prospective cohort study. Age-matched healthy subjects (n = 10) and stroke patients (n = 10). Various kinematic indices were analysed from 3 randomly assigned tasks performed by the affected arm in stroke patients and the dominant arm in healthy subjects. These tasks, composed of large-amplitude, targeted and geometrical movements, were standardized and performed with the ReaPLAN robotic device. For large-amplitude movements, the stroke patients' path lengths were less constant in amplitude, less rectilinear and less smooth than those for healthy subjects (p < 0.001). For the targeted movements, the stroke patients' path lengths were less rectilinear than those of the healthy subjects (p < 0.001). For the geometrical movements, the stroke patients had greater difficulty making the requested shapes compared with the healthy subjects (p < 0.01). Our study proposes an objective and standardized protocol to assess stroke patients' upper limbs with any robotic device. We suggest that further randomized controlled trials could use this quantitative tool to assess the efficacy of treatments such as robot-assisted therapy.